Great Power-Middle Power Dynamics: The Case of China and Iran. Issue 117 (4th May 2019) - Conduit, Dara; Akbarzadeh, Shahram
ABSTRACT: Iran is expected to be one of the main beneficiaries of China's Belt and Road Initiative (BRI). China and Iran had a track record of cooperation long before the announcement of BRI, developing a highly asymmetric Great Power-Middle Power partnership over the course of three decades. This article asks whether BRI will enable China and Iran to transcend the limitations faced by most Great Power-Middle Power relationships on the basis of Iran's enhanced strategic economic and geographic value. It is argued that while BRI could benefit from stronger China–Iran ties, Iran's international posturing has proven a significant hindrance to China, highlighting that entrenched patterns of engagement in Great Power-Middle Power relations are not easily shifted, even in the face of immense economic incentives.